2016
DOI: 10.1186/s13071-016-1750-8
|View full text |Cite
|
Sign up to set email alerts
|

Could Phlebotomus mascittii play a role as a natural vector for Leishmania infantum? New data

Abstract: BackgroundThe occurrence of phlebotomine sand flies in Central Europe was questioned until they were recorded for the first time in Germany in 1999, and ten years later also in Austria. The aim of this study was to investigate sand flies collected in Austria for their carrier status of Leishmania spp.FindingsFrom 2012 to 2013 field studies were conducted in eastern Austria. Altogether, 22 individuals of sand flies were found, all morphologically identified as Phlebotomus (Transphlebotomus) mascittii Grassi, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
2
43
0
1
Order By: Relevance
“…Leishmania infantum and Leishmania tropica are already established in southern European countries 7 . An increase in the introduction of rescued stray dogs, main reservoir hosts of Leishmania parasites, from these areas leads to a spread of the parasites further north 27 . Despite several vector sandfly species and parasitic Leishmania species already established in Europe, leishmaniasis is still a largely understudied topic in Central and Northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania infantum and Leishmania tropica are already established in southern European countries 7 . An increase in the introduction of rescued stray dogs, main reservoir hosts of Leishmania parasites, from these areas leads to a spread of the parasites further north 27 . Despite several vector sandfly species and parasitic Leishmania species already established in Europe, leishmaniasis is still a largely understudied topic in Central and Northern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Despite isolated findings of P. mascittii in Germany, the vector competence of this sand fly species for Leishmania has not been verified yet. A recent study from Austria found L. infantum DNA in one P. mascittii, but did not provide evidence of metacyclic promastigotes or prove of transmission through experimental infections (Obwaller et al 2016). Prospective examinations were conducted in Urbach and Schwanstetten (location of the two DNA positive dogs presumably infected in Germany) by analyzing conjunctival swabs from 16 and 29 dogs, respectively, presented in the same clinics for various reasons.…”
Section: Leishmaniamentioning
confidence: 99%
“…in non-engorged females implies the presence of parasites that survived the blood meal digestion, and which became metacyclic infective forms. 86,87 In this study we did not separate engorged and non-engorged females for Leishmania spp. detection.…”
Section: Discussionmentioning
confidence: 94%